Alternatives for coexistence of GM and organic cotton production in Uganda - Gruère, Guillaume P. (International Food Policy Research Institute, 2013)
Cotton is Uganda’s third-largest export crop after coffee and tea (Baffes 2009). Although exports have fluctuated over time (see Figure 7.1), about 87 percent of the cotton lint produced in Uganda between 1996 and 2007 was exported. Despite low volumes of exports compared to other countries, the high proportion of cotton exported demonstrates the importance of trade in all cotton matters. In this context, it is legitimate to ask whether the introduction of genetically modified (GM) cotton would have any effect on Uganda’s cotton exports. This chapter provides a brief analysis of this question, using available data, results from the literature, and the study’s own assessment of the challenges ahead.